The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cmdc.202000185
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Evaluation of 2,4‐Diaminoquinazoline Derivatives as Potential Tubulin Polymerization Inhibitors

Abstract: Microtubules are highly dynamic polymers composed of αand β-tubulin proteins that have been shown to be potential therapeutic targets for the development of anticancer drugs. Currently, a wide variety of chemically diverse agents that bind to β-tubulin have been reported. Nocodazole (NZ) and colchicine (COL) are well-known tubulin-depolymerizing agents that have close binding sites in the β-tubulin. In this study, we designed and synthesized a set of nine 2,4-diaminoquinazoline derivatives that could occupy bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(61 reference statements)
1
2
0
1
Order By: Relevance
“…Paclitaxel ( PTX ) was included as a positive control since this compound stabilizes microtubules in the growth phase. The V max value of 47.0 mOD/min indicates the absence of the nucleation phase and rapid growth, consistent with previous experiments . Conversely, NZ inhibits the growth phase ( V max = 6.0 mOD/min), leading to a V max 3.5 times lower than that of the control.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Paclitaxel ( PTX ) was included as a positive control since this compound stabilizes microtubules in the growth phase. The V max value of 47.0 mOD/min indicates the absence of the nucleation phase and rapid growth, consistent with previous experiments . Conversely, NZ inhibits the growth phase ( V max = 6.0 mOD/min), leading to a V max 3.5 times lower than that of the control.…”
Section: Resultssupporting
confidence: 90%
“…Although the replacement of naphthyl with quinoline resulted in a decrease in the binding free energy, the incorporation of chlorine at position 5 ( 5d ) or methyl at position 2 ( 5e ) in this heterocycle showed an improvement in the affinity. Compound 5d was incorporated to the perturbation map since in a recent work we found that a quinazoline derivative comprising the 5-chloroquinoline substituent exhibited the best antiproliferative activity against the SK-LU-1 cell line (IC 50 = 5.0 ± 0.2 μM) and inhibited the tubulin polymerization rate in a concentration-dependent manner . In the same study, we suggested that the 5-chloroquinoline substituent was positioned toward the COL pocket, resulting in an increased number of hydrophobic interactions.…”
Section: Resultsmentioning
confidence: 93%
“…[31] Hernandez-Luiz and his team synthesized a series of novel 2,4-diaminoquinazoline derivatives and evaluated their anticancer activity against five cancer cell lines, namely PC-3, HCT-15, MCF-7, MDA-MB-231, and SK-LU-1. [32] Among them, compounds 1 (bearing 3-Chlorophenoxy) and 2 (bearing 5chloroquinolin-8-yl) showed promising anti-proliferative activity by inhibiting tubulin polymerization. At 10 μM concentration, compound 1 exhibited a tubulin polymerization curve similar to that of nocodazole.…”
Section: Quinazoline Derivatives As Tubulin Polymerization Inhibitorsmentioning
confidence: 99%
“…синтезированные производные 2,4-диаминохиназолина проявляют антипролиферативную активность, ингибируя полимеризацию тубулина. [31].…”
Section: потенциальные лекарственные средстваunclassified